A clinical observational study of dinutuximab beta as first-line maintenance treatment for patients with high-risk neuroblastoma in China - Xuedi Yu; Suyi Kang; Junjie Ge; Jingfu Wang (BMC Pediatrics)
Abstract Background High-risk neuroblastoma (HR-NB) is associated with high metastatic and relapse rates that require intensive multimodal treatment. We evaluated the efficacy and safety of dinutuximab beta as first-line maintenance immunotherapy in pediatric patients with HR-NB in real-world clinical settings in China. Methods We retrospectively reviewed the clinical records of pediatric patients with newly diagnosed HR-NB in the hospital from October 2021 to November 2023. Patients treated with dinutuximab beta in combination with granulocyte-macrophage colony-stimulating factor (GM-CSF) and isotretinoin as the first-line maintenance therapy were included in this study. Among patients with residual disease after completing induction and consolidation treatment, those with partial response (PR) or very good partial response (VGPR) except for bone marrow (BM) residue were also administrated vincristine/irinotecan/temozolomide (VIT) chemotherapy. Results Fifty-one patients with newly diagnosed HR-NB who achieved at least PR before immunotherapy were evaluated. At the end of immunotherapy, the objective response rate (ORR) in 33 patients with evidence of disease was 60.6% (95% confidence interval (CI), 42.1-77.1%) and the complete response rate (CRR; n = 18) was 54.5% (95% CI, 36.4-71.9%). The 2-year event-free survival (EFS) rate and overall survival (OS) rate were 80.1% (95% CI, 66.2-88.8%) and 97.6% (95% CI, 84.3-99.7%), respectively. The 2-year EFS rate was higher in patients with CR (94.4%; 95% CI, 66.6-99.2%) than in non-CR patients (72.6%; 95% CI, 53.9-84.7%). Dinutuximab beta was well tolerated in patients and had fewer side effects, which decreased over time. Co-treatment of dinutuximab beta with VIT chemotherapy did not require discontinuation in patients undergoing immunochemotherapy. Conclusion The study showed promising efficacy and safety of dinutuximab beta as the first-line maintenance immunotherapy for pediatric patients with HR-NB. Notably, the combination of dinutuximab beta with GM-CSF and VIT chemotherapy could be used for treating patients who did not achieve CR after previous multimodal therapy.